Unmasking Denial in Symptomatology: Delving into the Psychological, Sociocultural, and Contextual Factors of Denial of Patient Symptoms - Sharma, Saksham Sharma; Khanna, Sukul; Reshi, Amrutha; Shah, Dhruvi; Pothiwala, Aayush; Nair, Shreya; Sajja, Joshua (International Journal of Clinical Research, 2024)
Background: Symptom denial is a multifaceted response, intricately woven with individual psychology, societal pressures, and environmental cues. This Narrative review delves into this complexity, spotlighting the critical role of a patient’s mindset in determining their acceptance or denial of a disease. Objectives: The literature aims to elucidate the denial of symptoms and its various underlying factors to make healthcare more inclusive of these variations in patient presentations. Methods: A literature search was conducted across the PubMed database, and hand searches were done on Google Scholar to acquire literature based on SANRA guidelines with structured inclusion and exclusion criteria. Results: The culmination of this exploration underscores the intricate nature of symptom denial, revealing its multifaceted origins within individual psychology, societal norms, and the broader environment. Denial emerges not as a monolithic reaction but as a nuanced interplay of coping mechanisms, cultural beliefs, socioeconomic factors, and health literacy. Discussion: Acknowledging these complexities is vital for tailored healthcare approaches. By unraveling the layers of denial, we pave the way for informed interventions that respect diverse perspectives and foster improved symptom acknowledgment, ultimately enhancing overall well-being and patient outcomes.